Gender, Age and Reproductive Status Effects on Serum Prolactin Concentrations in Different Varieties and Species of Poultry - Edens , F.W. (International Journal of Poultry Science, 2011)
Homologous chicken prolactin (chPRL) and turkey prolactin (trPRL) radioimmunoassays were used to assess the effects of gender, age and reproductive status on serum prolactin concentrations in several varieties and species of poultry. Adult males (chickens, turkeys [domestic and wild], Coturnix quail and chukar partridges had lower serum prolactin (PRL) concentrations than did their female counterparts. Aging in meat-type female chickens appeared to be associated with increasing PRL concentrations, but aging of White Leghorn chickens did not result in increased serum prolactin concentrations. Aging in males did not alter serum prolactin concentrations. In female chukar partridges, serum prolactin concentrations were similar to that of White Leghorn hens and male chukar serum prolactin concentrations were similar to levels found in male chickens. Serum prolactin concentrations in Coturnix males and females, with females having greater serum prolactin than males, were generally higher than in males and females of other fowl involved in this study. Broodiness was associated with greatly elevated serum prolactin concentrations. The serum prolactin concentrations derived from the use of the chPRL assay as a heterologous assay for chukar and domestic and wild turkeys, yielded results that were lower but in parallel with results from trPRL assay. The homologous chicken PRL radioimmunoassay appeared to be useful as a heterologous assay for domestic and wild turkey and for chukar partridge PRL.